Impact of Fungicide Timing on the Composition of the Fusarium Head Blight Disease Complex and the Presence of Deoxynivalenol (DON) in Wheat - Audenaert, Kris; Landschoot, Sofie; Vanheule, Adriaan; Waegeman, Willem; Baets, Bernard De; Haesaert, Geert (IntechOpen, 2011)
None